Wear prediction on total ankle replacement : effect of design parameters /: effect of design parameters. (2016) - Amir Putra bin Md Saad; Ardiyansyah Syahrom; Muhamad Noor Harun; Mohammed Rafiq Abdul Kadir
No abstract available